1996
DOI: 10.1042/bj3150665
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for differences in the post-transcriptional regulation of rat metallothionein isoforms

Abstract: The expression of metallothionein (MT)-1 and -2 mRNAs in rat liver following administration of Cd or Cu was investigated using specific oligonucleotides. The specificity was confirmed using a competitive prehybridization assay. Cd injection caused a biphasic induction of both isoform mRNAs, whereas Cu induced a sustained, monophasic response. Analysis of polyribosomal RNA showed that, after both Cd and Cu treatments, the recruitment of MT-1 mRNA into polyribosomes paralleled the increase in transcription, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 35 publications
2
25
2
Order By: Relevance
“…As previously reported Cherian, 1981, 1982;Vasconcelos et al, 1996;Iszard et al, 1995;Eaton et al, 1980;Klaassen and Liu, 1998;Kotsonis and Klaassen, 1978;Schnell et al, 1978), the increase of the MT level was very high in the liver, however, our results showed that MT induction occurred with lower doses of Cd than those used in the literature and these did not lead to the significant toxicity demonstrated by clinical signs. This increase of the hepatic MT level appeared from 12 h which is in accordance with the rapid (5 h) increase of hepatic MT mRNA reported by Vasconcelos et al (1996), and was maintained or was even higher until 72 h. This has not been described in the literature. The highest response of the liver compared with the kidney has been described with higher doses of Cd, i.e.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…As previously reported Cherian, 1981, 1982;Vasconcelos et al, 1996;Iszard et al, 1995;Eaton et al, 1980;Klaassen and Liu, 1998;Kotsonis and Klaassen, 1978;Schnell et al, 1978), the increase of the MT level was very high in the liver, however, our results showed that MT induction occurred with lower doses of Cd than those used in the literature and these did not lead to the significant toxicity demonstrated by clinical signs. This increase of the hepatic MT level appeared from 12 h which is in accordance with the rapid (5 h) increase of hepatic MT mRNA reported by Vasconcelos et al (1996), and was maintained or was even higher until 72 h. This has not been described in the literature. The highest response of the liver compared with the kidney has been described with higher doses of Cd, i.e.…”
Section: Discussionsupporting
confidence: 44%
“…This increase in the concentration of MT can be considered as induced synthesis of MT in these tissues because an intracellular protein such as MT is not transferred from one organ to another during the short experimental period of the study (Onosaka and Cherian, 1982). As previously reported Cherian, 1981, 1982;Vasconcelos et al, 1996;Iszard et al, 1995;Eaton et al, 1980;Klaassen and Liu, 1998;Kotsonis and Klaassen, 1978;Schnell et al, 1978), the increase of the MT level was very high in the liver, however, our results showed that MT induction occurred with lower doses of Cd than those used in the literature and these did not lead to the significant toxicity demonstrated by clinical signs. This increase of the hepatic MT level appeared from 12 h which is in accordance with the rapid (5 h) increase of hepatic MT mRNA reported by Vasconcelos et al (1996), and was maintained or was even higher until 72 h. This has not been described in the literature.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…While there is evidence of transcriptional control of MT expression at gene level, there is only little evidence of post-transcriptional regulation of MT synthesis (Vasconcelos et al, 1996). The mechanism of translational control of MT synthesis is still unknown, but, probably, it may require the participation of specific protein factors interacting with MT mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…However, regulation at the translational level whether synthesis or degradation of MT should be considered. Vasconcelos et al [2002], have shown that the levels in liver and testes can also be markedly different through this mechanism [Vasconcelos et al 1996] perhaps rendering the testes more susceptible to Cd toxicity than liver.…”
Section: Resultsmentioning
confidence: 99%